2014
DOI: 10.1007/s40333-014-0062-0
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for the links between the local water cycle and the underground wet sand layer of a mega-dune in the Badain Jaran Desert, China

Abstract: Scientists and the local government have great concerns about the climate change and water resources in the Badain Jaran Desert of western China. A field study for the local water cycle of a lake-desert system was conducted near the Noertu Lake in the Badain Jaran Desert from 21 June to 26 August 2008. An underground wet sand layer was observed at a depth of 20-50 cm through analysis of datasets collected during the field experiment. Measurements unveiled that the near surface air humidity increased in the nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…While applying the theory by Philip and De Vries (), traditional coupled water and energy models that simulate states in the unsaturated zone widely disregard the flow of the gas phase (Zeng et al, ). Nevertheless, the gaseous phase (water vapor and dry air) flow mechanism has been shown to substantially enhance the vapor transport in arid regions (Wen et al, ; Zeng, ; Zeng, Su, et al, ; Zeng, Wan, et al, ; Zeng & Su, ). This has led to the development of multiphase models such as STEMMUS (Zeng et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…While applying the theory by Philip and De Vries (), traditional coupled water and energy models that simulate states in the unsaturated zone widely disregard the flow of the gas phase (Zeng et al, ). Nevertheless, the gaseous phase (water vapor and dry air) flow mechanism has been shown to substantially enhance the vapor transport in arid regions (Wen et al, ; Zeng, ; Zeng, Su, et al, ; Zeng, Wan, et al, ; Zeng & Su, ). This has led to the development of multiphase models such as STEMMUS (Zeng et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…the desert lakes are mainly recharged by groundwater, and the local rainfall is not the major replenishment source of the groundwater and lakes. Wen et al (2014) observed the local water cycle near the Nuoertu Lake for three months with automatic weather station and eddy covariance system in the Badain Jaran Desert in 2008. Three rainfalls with the total precipitation of 50.0 mm occurred during 17 days, but the average volumetric sand moisture below 60 cm remained lower than 6% and had no variation throughout.…”
Section: Moisture and Stable Isotopes Of Sand Profilesmentioning
confidence: 99%
“…The few hydrometeorological observations (Gu et al, 2004;Wen et al, 2014) in the desert were only short term or discontinuous because of the extreme conditions, which has led to controversial interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the turbulent LE fluxes is driven primarily by wind velocity, the specific humidity (vapour pressure deficit) gradients between the air and the surface and surface conditions (e.g. surface roughness and vegetation period) (Vickers et al, 2010;Tang et al, 2014;Wen et al, 2014). The annual LE and AtmH 2 O patterns showed that the mean LE and AtmH 2 O values of the growing season were on average sevenfold and twofold greater than those of the non-growing season, respectively.…”
Section: Extreme Eventsmentioning
confidence: 99%